2014
DOI: 10.1016/j.nbd.2014.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neutrophil antibody enhances the neuroprotective effects of G-CSF by decreasing number of neutrophils in hypoxic ischemic neonatal rat model

Abstract: Objectives Neonatal hypoxia ischemia (HI) is an injury that can lead to neurological impairments such as behavioral and learning disabilities. Granulocyte-colony stimulating factor (G-CSF) has been demonstrated to be neuroprotective in ischemic stroke however it has also been shown to induce neutrophilia, ultimately exacerbating neuronal injury. Our hypothesis is that coadministration of anti-neutrophil antibody (Ab) with G-CSF will decrease blood neutrophil counts thereby reducing infarct volume and improving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…Although the onset varies, the intracerebral neutrophil infiltration is found in all types of cerebral ischemic injury [8]. Accumulating evidence suggests this intracerebral neutrophil infiltration has potentially damaging pro-inflammatory consequences in cerebral ischemia and highlights a crucial role of neutrophils in the prevention and treatment of stroke [5,7,9,10]. A recent study also showed that neutrophils and neutrophil-derived iNOS contribute to ischemic brain injury [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the onset varies, the intracerebral neutrophil infiltration is found in all types of cerebral ischemic injury [8]. Accumulating evidence suggests this intracerebral neutrophil infiltration has potentially damaging pro-inflammatory consequences in cerebral ischemia and highlights a crucial role of neutrophils in the prevention and treatment of stroke [5,7,9,10]. A recent study also showed that neutrophils and neutrophil-derived iNOS contribute to ischemic brain injury [26].…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of neutrophils to brain parenchyma is found in ischemic brain injury [8]. The neutrophil-to-lymphocyte ratio is a prognostic marker in ischemic cerebrovascular diseases and the depletion or functional inhibition of neutrophils leads to decreased neuroinflammation and neuronal apoptosis in stroke subjects [5,7,9,10]. Despite the potential compromise of the bloodbrain barrier (BBB) in ischemic brain injury, this structure still remains a determinant barrier of therapeutic drug feasibility.…”
Section: Introductionmentioning
confidence: 99%
“…In term infants with HIE, the significantly elevated number of peripheral neutrophils in the first 96 hours of life is associated with the poor neurodevelopmental outcomes (Morkos et al , 2007). A recent study suggests that the neuroprotective effects of granulocyte colony-stimulating factor (G-CSF) may be further enhanced if the peripheral neutrophils are depleted in a rat neonatal HI model (Doycheva et al , 2014). Hence, neutrophils contribute to the exacerbation of neonatal brain damage, even though they do not rapidly accumulate in the developing brain after hypoxia-ischemia.…”
Section: The Role Of Innate Immune Cells In Neonatal Hi Brain Injurymentioning
confidence: 99%
“…However, it promotes the development of neutrophilic granulocytes and leads to neutrophilia, which may ultimately exacerbate neuronal injury. Doycheva et al have demonstrated that administration of anti-neutrophil antibody with GCSF after cerebral hypoxia-ischemia reduces the brain injury and significantly improves neurological function by decreasing blood neutrophil accumulation in a neonatal rat model (Doycheva et al , 2014). Thus, anti-neutrophil strategies would be more effective in neonatal rats when co-administration of anti-neutrophil antibody with other anti-inflammatory and/or antiapoptotic candidates, such as G-CSF.…”
Section: Bench To Bedside: Promising Anti-inflammatory/immunomodulmentioning
confidence: 99%
“…Ischemic-brain-injury models have demonstrated that G-CSF treatment can reduce neuroinflammation, neutrophil infiltration, infarct volume and blood–brain barrier (BBB) disruption (Lee et al, 2005; Doycheva et al, 2014; Li et al, 2015). Evidence from rAION models suggests that reducing inflammation and ON edema in the acute phase may be effective in protecting neurons from degeneration (Goldenberg-Cohen et al, 2005; Slater et al, 2008; Zhang et al, 2009, 2010; Touitou et al, 2013; Chang et al, 2014; Lee et al, 2014).…”
Section: Introductionmentioning
confidence: 99%